Effectiveness of Some Simple Techniques for Fly Ash Beneficiation - Kaur, Amanpreet (My University, 2012)
Fly ash, generated during the combustion of coal for energy production, is an industrial by-product which is recognized as an environmental pollutant. Because of the environmental problems created by the fly ash, considerable research has been undertaken on the subject worldwide. The utilization of fly ash in construction, as a low-cost adsorbent for the removal of organic compounds, flue gas and metals, light weight aggregate, mine back fill, road sub-base, and zeolite. Fly ash beneficiation is the separation of carbon particles. High unburned carbon content in the fly ash makes it unsuitable for use as cement admixture. High carbon results in discoloration, poor air entrainment and segregation of mix components. Beneficiation is required to enhance the ability to extract high purity carbon and ash for the production of value-added products. Beneficiation techniques are based on the differences in size, density, electrostatic and physical properties of the particles. Fly ash beneficiation techniques are:triboelectrostaticseparation, ultrasonic column agglomeration, and column flotation, froth flotation, air classifier,magnetic separation and gravity separation, fluidized bed separation etc. In the present study, fly ash from NFL Nangal, India, having LOI ~ 15%, is subjected to the simple beneficiation techniquesnamely froth flotation and fluidization. The equipment for conducting the experiments wereself fabricated/designed. Using froth floatation the LOI of fly ash could be reduced to ~10%. The effectiveness of screening followed by froth floatation showed promising results, and LOI of fly ash could be reduced to ~ 8%. Fluidized bed separation, being a dry separation process, is an attractive alternative. The results for fluidized bed separator showed LOI reduction to ~ 11%. The experimental observations indicated that a shallow fluidized bed shall give better separation than a deep fluidized bed.
M.Tech. (Chemical Engineering)
Keywords: Fly ash; Cement Admixture; Beneficiation